The sansevieria trifasciata fiber compatibility analysis for biocomposite reinforcement - Edi Widodo; Mulyadi Mulyadi; Prantasi Harmi Tjahjanti; Fajar Syahril Kirom (TURBO [Tulisan Riset Berbasis Online], 2021)
This study analyzes the potential of sanseviera fibers to be used as biocomposite reinforcement. Sansevieria fibers are characterized to improve physical and chemical properties so that they are stronger and can be used as a reinforcement for the composite matrix. Fiber alkaline treatment with NaOH solution, proven to remove hemicellulose and lignin content, improve fiber properties, can increase the adhesiveness properties of the resin matrix. The fiber that has been treated with alkali is used as a bio-composite reinforcement using an epoxy resin matrix. FTIR test was carried out to obtain data from the compound groups of the fibers. Cellulose and hemicellulose contents were analyzed and the degree of crystallinity of the fibers to obtain compatibility with epoxy resin as a matrix. Chemical properties of Sansevieria fibers. Compared to PET and PETG fibers, as a composite reinforcing synthetic fiber with good compatibility with resins. This compatibility will determine the homogeneity of the adhesive properties of the fiber surface to the matrix. The bonding of microstructural compounds is very dependent on this property and will give the final result a better tensile strength of the composite.Keywords: biocomposite, sansevieria fibre, epoxy resin.